Reduced Graphene Oxide Decorated Na3V2(PO4)3 Microspheres as Cathode Material With Advanced Sodium Storage Performance - Chen, Hezhang; Huang, Yingde; Mao, Gaoqiang; Tong, Hui; Yu, Wanjing; Zheng, Junchao; Ding, Zhiying (Frontiers in Chemistry, 2018)
Reduced graphene oxide (rGO) sheet decorated Na3V2(PO4)3 (NVP) microspheres were successfully synthesized by spray-drying method. The NVP microspheres were embedded by rGO sheets, and the surface of the particles were coated by rGO sheets and amorphous carbon. Thus, the carbon conductive network consisted of rGO sheets and amorphous carbon generated in the cathode material. NVP microspheres decorated with different content of rGO (about 0, 4, 8, and 12 wt%) were investigated in this study. The electrochemical performance of NVP exhibited a significant enhancement after rGO introduction. The electrode containing about 8 wt% rGO (NVP/G8) showed the best rate and cycle performance. NVP/G8 electrode exhibited the discharge capacity of 64.0 mAh g−1 at 70°C, and achieved high capacity retention of 95.5% after cycling at 10°C for 100 cycles. The polarization of the electrode was inhibited by the introduction of rGO sheets. Meanwhile, compared with the pristine NVP electrode, NVP/G8 electrode exhibited small resistance and high diffusion coefficient of sodium ions.